Conveying the Meaning through Experiential Metafunction on Song Lyrics: A Case on Ideational Metafunction - Sinaga, Yanti Kristina; Murni Situmorang, Natalia; Purba, Elprinawati; Sitompul, Heppy Theresia; Panjaitan, Anita; Herman, Herman; Thao, Nguyen Van (CV. Creative Tugu Pena, 2023)
This research explores the song